Place and student subjectivities in Higher Education 'cold spots'. Issue 3 (2nd April 2020) - Henderson, Holly
Abstract: This article uses an analytical framework informed by social geographies to explore the complex relationships between Higher Education Institution, undergraduate student and place. Drawing on findings from a qualitative study exploring the experiences of college-based Higher Education students studying degree courses in Further Education Colleges in England, the article sees student subjectivities as structured through inequalities of institutional positioning in a stratified system as well as through layered local histories of industrial loss. Taken as an instance of undergraduate education in a massified and geographically unequal national context, the findings in this article offer an insight into the contradictory role played by Higher Education in its local area, particularly where a local area is defined by both a lack of and a need for increased educational opportunity.